VD_FINDINFO Jug / 2021 / 349 vom 19. April 2021 - VD Tribunal cantonal (2021)
ACTE D'ORDRE SEXUEL AVEC UN ENFANT, TENTATIVEDROIT PÉNAL, PORNOGRAPHIE | 187 ch. 1 CP, 187 ch. 4 CP, 196 CP, 22 ad 187 ch. 1 CP, 22 ad 187 ch. 4 CP, 22 ad 196 CP, 22 ad 197 al. 4 CP